1992
DOI: 10.1080/00071669208417545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different rates of drying cassava root on its toxicity to broiler chicks

Abstract: 1. The effects of drying cassava root at different rates on its composition and toxicity to broiler chicks were examined. Unpeeled roots from a high-cyanide cultivar of cassava were chipped and dried at 25 degrees C to a moisture content of below 100 g/kg over 24 h for fast-dried meal (FD) or 72 h for slow-dried meal (SD). The meals were incorporated at 250 and 500 g/kg into semi-synthetic diets which were fed to day-old broiler chicks as mash or pellets in separate experiments. 2. The two drying rates produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 14 publications
1
14
0
3
Order By: Relevance
“…Phytic acid is the primary storage compound of phosphorus in plants, accounting for up to 80 per cent of the total phosphorus [30,31]. Phytic acid has been found in cassava root [32] and cocoyam tuber [13] up to levels of 62.4 and 1.75g/100g, respectively. Josefsen et al, [33] reported that the negatively charged phosphate in phytic acid strongly binds to metallic cations (e.g.…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…Phytic acid is the primary storage compound of phosphorus in plants, accounting for up to 80 per cent of the total phosphorus [30,31]. Phytic acid has been found in cassava root [32] and cocoyam tuber [13] up to levels of 62.4 and 1.75g/100g, respectively. Josefsen et al, [33] reported that the negatively charged phosphate in phytic acid strongly binds to metallic cations (e.g.…”
Section: Antinutritional Factorsmentioning
confidence: 99%
“…In this well documented study the authors state that the inclusion of cassava root meal in chick diets can result in watery excreta, which cause litter management problems and, therefore, might limit the use of the meal in some poultry production systems. Furthermore they found an apparent association of the intake ratio of water to food with the cyanogen content of the diet and noted that this may suggest that water intake is related to the mechanisms of cyanide toxicity or the detoxification of cyanogenic glucosides (Panigrahi et al, 1992). This study together with studies of Tewe (1984) and Gomez et al (1988) are reviewed by Garcia and Dale (1999), a review allowing the following conclusions:…”
Section: Adverse Effects In Poultrymentioning
confidence: 99%
“…However, once again, only few of them provide data on the content of cyanogenic compounds, although they do sometimes investigate the effect of adding sulfur in the form of elementary sulfur or as Na 2 SO 4 to ensure optimal conditions for in vivo detoxification (metabolism to thiocyanate) of ingested cyanide and cyanogens (Gowdh et al, 1990). Panigrahi et al (1992) found that cassava root meal of less than 40 mg total cyanide per kg meal can be fed to broiler chicks at 500 g/kg of total diet without any adverse effects. In this well documented study the authors state that the inclusion of cassava root meal in chick diets can result in watery excreta, which cause litter management problems and, therefore, might limit the use of the meal in some poultry production systems.…”
Section: Adverse Effects In Poultrymentioning
confidence: 99%
“…Por outro lado, há vários trabalhos na literatura, relatando que a exposição prolongada ao cianeto, em baixas concentrações, pode ocasionar quadros de toxicidade crônica. De fato, em humanos, foi comprovada a associação entre a exposição crônica ao cianeto na etiologia de alguns distúrbios neurológicos, tais como neuropatia atáxica tropical 7 , konzo 8 , neuropatia retrobular da anemia perniciosa 9 e atrofia óptica de Leber 10,11 . Na criação animal, a ingestão crônica do cianeto tem sido associado a diversas doenças, como a cistite e ataxia enzoótica, uma síndrome caracterizada pela presença de degeneração walleriana da substância branca da medula espinhal e de degeneração de pedúnculos cerebrais e cerebelares 12,13,14 .…”
Section: Introductionunclassified